HUBUNGAN ANTARA MOTIVASI DENGAN PERILAKU SELF PROTECTION PADA KELUARGA PENDERITA TB PARU DI PUSKESMAS UMBULHARJO I YOGYAKARTA - istichomah; Babu Handa Praing; Salis Miftahul. Khoeriyah (Jurnal Kesehatan Madani Medika (JKMM), 2018)
died of Pulmonary TB. The risk of transmission of pulmonary TB every year increase. The family is the nearest person who has a high risk of contracting TB disease. Therefore, family of pulmonary patient should have a motivation in self-protection effort or prevention of transmission to family member. Family motivation determines the success of the treatment, especially in preventing transmission, because if the behavior of the client's family who is diagnosed with pulmonary TB understands what he actually does then indirectly the family can protect himself and other family members. This study aims to determine the correlation between motivation with self- protection behavior for the sufferer family of the pulmonary TB in Public Health Center of Um- bulharjo I Yogyakarta. This research is a quantitative research with the research design is an analytical survey and cross-sectional approach, conducted in September 2017. The population in this research is a family of Pul- monary TB in Public Health Center of Umbulharjo I Yogyakarta, amounting to 32 people, the sampling tech- nique used a total sampling. The data analysis used a Kendal tau, to know the motivation with self-protection behavior in family of pulmonary TB patient. Results: The results of this study indicate that there is a correlation motivation with self-protection behavior for the sufferer family of the pulmonary TB in Public Health Center of Umbulharjo I Yogyakarta. With the value of Kendal Tau significantly as 0,004< 0,05. The correlation between motivation with self-protection behavior for the sufferer family of the pulmonary TB in Public Health Center of Umbulharjo I Yogyakarta. It is expected that family can increase the motivation, as effort to prevent the transmission of pulmonary TB to other family mem- ber.